2014
DOI: 10.1002/jsfa.6827
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation with lactic acid bacteria to improve the nutritional quality of lupin and soya bean

Abstract: SSF improved lupin and soya bean protein digestibility. BLIS-producing LAB in lupin and soya bean medium produced a mixture of D- and L-lactic acid with a major excess of the latter isomer. Most toxic histamine and tyramine in fermented lupin and soya bean were found at levels lower those causing adverse health effects. Selection of biogenic amines non-producing bacteria is essential in the food industry to avoid the risk of amine formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 44 publications
(88 reference statements)
2
45
0
1
Order By: Relevance
“…The in vitro digestibility of proteins depends on the type of fermentation (solid state or submerged fermentation), the type of microorganisms and the type of legume (Bartkiene et al, 2015). The low digestibility of plant proteins together with the limited content of essential amino acids result in a low nutritional value compared to animal proteins (Carbonaro et al, 2012).…”
Section: The Application Of Lacto-fermentation To Improve the Nutritimentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro digestibility of proteins depends on the type of fermentation (solid state or submerged fermentation), the type of microorganisms and the type of legume (Bartkiene et al, 2015). The low digestibility of plant proteins together with the limited content of essential amino acids result in a low nutritional value compared to animal proteins (Carbonaro et al, 2012).…”
Section: The Application Of Lacto-fermentation To Improve the Nutritimentioning
confidence: 99%
“…Previous digestibility studies of protein obtained from legumes have shown interactions between antinutritional compounds, such as trypsin inhibitors and tannins, and the decreased proteolytic susceptibility of protein complexes, thereby decreasing the food value of plant proteins (Agte et al, 1998). The digestibility of lupin protein could be improved by lactic acid fermentation (Bartkiene et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However the formation of organic acids depended on the type of fermentation, duration, temperature, substrate and LAB strain. 48,102 LAB is more acid tolerant compared to other types of bacteria and are more tolerant to a lower and wider pH range (Table 6). It is well known that culture pH greatly inuenced the growth of LAB and bacteriocin production apart from inu-encing cell aggregation, cell absorption of bacteriocin and/or proteolytic degradation.…”
Section: Phmentioning
confidence: 99%
“…Bartkiene et al . () reported that compared to untreated sample, protein digestibility of fermented soya bean was found to be higher on average by 15.9%. It could be speculated that the partial loss of compact protein structure and the degradation of some polypeptide chains may be responsible for the improvement of protein digestibility, as evidenced by SDS‐PAGE profile (Fig.…”
Section: Resultsmentioning
confidence: 96%